Evaluation of wound healing activities between melastoma malabathricum leaves extract and chromolaena odorata leaves extract in male sprague dawley rats / Siti Muzaifah Mustapa - Mustapa, Siti Muzaifah (2015)
Melastoma malabathricum and Chromoalaena odorata are traditional remedies used by Asian, generally to heal the wound. To date, no data on comparison of percentage wound healing between Melastoma malabathricum leaves extract and Chromolaena odorata leaves extract been studied. Current study was designed to compare wound healing activities between M.malabathricum leaves extract and C.odorata leaves extract in vivo. Phytochemical analysis for both herbal plants also had been done by using methanol solvent to determine concentration of flavonoid and tannin. Sixteen male Sprague dawley rats used as excisional wound model and wound was created with area 4cm2 on their dorsal by using scalpel after acclimatized for two weeks. They were divided to four groups whereby each group was gave different treatment that were group I: gentamicin cream, group II: 10% Melastoma malabathricum ointment, group III: 10% Chromolaena odorata ointment and group IV: Vaseline and in three days interval until fifteenth day percentage of wound area was measured and calculated. M. malabathricum leaves extract consist higher concentration of flavonoids and tannins compare to the C. odorata leaves extract and visually, M. malabathricum leaves extract accelerate wound healing faster than C. ododrata leaves extract, as the concentration of flavonoids and tannins were high. Statistically the result was not significant. In conclusion, M. malabathricum leaves extract and C. odorata leaves extract do show potential asset that can be used for development of alternative remedy.